Trapping a salt-dependent unfolding intermediate of the marginally stable protein Yfh1 - Vilanova, Bartolomé; Sanfelice, Domenico; Martorell, Gabriel; Temussi, Piero A.; Pastore, Annalisa (Frontiers in Molecular Biosciences, 2014)
Yfh1, the yeast ortholog of frataxin, is a protein of limited thermodynamic stability which undergoes cold denaturation at temperatures above the water freezing point. We have previously demonstrated that its stability is strongly dependent on ionic strength and that monovalent or divalent cations are able to considerably stabilize the fold. Here, we present a study of the folded state and of the structural determinants that lead to the strong salt dependence. We demonstrate by nuclear magnetic resonance that, at room temperature, Yfh1 exists as an equilibrium mixture of a folded species and a folding intermediate in slow exchange equilibrium. The equilibrium completely shifts in favor of the folded species by the addition of even small concentrations of salt. We demonstrate that Yfh1 is destabilized by a localized energetic frustration arising from an “electrostatic hinge” made of negatively charged residues mapped in the -sheet. Salt interactions at this site have a ”frustration-relieving” effect. We discuss the consequences of our findings for the function of Yfh1 and for our understanding of protein folding stability.